Sociocultural Component of Teachers’ Professional Competence - Stakhiv, Maria; Boiko , Halyna (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
This article considers the theoretical and practical issues of sociocultural competence of Ukrainian students of higher educational institutions; the priorities of the sociocultural education paradigm were analyzed; in this context, the issue of training future teachers to work in terms of a personality oriented teaching approach was presented. On the basis of the analysis conducted on psycho-pedagogical and methodological literature that covers the raised problems, a number of methodological and pedagogical ideas which provide for the formation of social and cultural mobility of future teachers were determined in order to ensure pupils’ sociocultural development